Peran Lingkungan Kerja dalam Meningkatkan Kepuasan Kerja Karyawan Pabrik Rokok - Refi Dwi Firli; Mudji Kuswinarno (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to explore the role of work environment in improving employee job satisfaction in a cigarette factory using a descriptive method with a qualitative approach. Data was collected through interviews with 10 cigarette factory employees. This approach allows for a more in-depth understanding of employees' perceptions of their work environment that affects job satisfaction. The results revealed that the work environment has a significant effect in increasing employee job satisfaction. The conclusion of this study emphasizes the importance of cigarette factory management to pay attention to and improve the quality of the work environment from various aspects in order to increase employee job satisfaction.